2020
DOI: 10.3389/fncel.2020.00154
|View full text |Cite
|
Sign up to set email alerts
|

Dyslipidemic Diet Induces Mobilization of Peripheral Neutrophils and Monocytes That Exacerbate Hemorrhagic Brain Injury and Neuroinflammation

Abstract: Background: Non-alcoholic fatty liver disease (NAFLD) is a common liver condition characterized by a significant accumulation of lipids in the liver without excessive alcohol consumption. Accumulating evidence suggests a significantly increased risk of intracerebral hemorrhage (ICH) in NAFLD patients. However, it remains poorly understood whether and how NAFLD affects the outcome of hemorrhagic brain injury. Here, we examined the effects of diet-induce NAFLD on ICH injury and neuroinflammation in mice. Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 39 publications
2
14
0
Order By: Relevance
“…Similarly, exacerbated neuroinflammation and intracerebral hemorrhage injury was previously observed in a mouse model of NAFLD 56 . Moreover, recruited neutrophils to tissue injury migrate at a higher speed in NASH larvae.…”
Section: Discussionsupporting
confidence: 62%
“…Similarly, exacerbated neuroinflammation and intracerebral hemorrhage injury was previously observed in a mouse model of NAFLD 56 . Moreover, recruited neutrophils to tissue injury migrate at a higher speed in NASH larvae.…”
Section: Discussionsupporting
confidence: 62%
“…Collectively, these studies indicate that NASH is associated with impaired spatial learning and memory as well as depression-like behaviour, and that these neurobehavioral changes are accompanied by microglia activation and increased release of proinflammatory cytokines in brain tissue [ 61 , 62 , 63 ]. Furthermore, the induction of NAFLD in models of Alzheimer’s disease (AD) and haemorrhagic brain injury exacerbates cognitive impairment and neuroinflammation [ 64 , 65 ]. In human NAFLD, chronic neuroinflammation was suggested by Balzano et al, who studied post-mortem cerebellums of NASH patients and found neuronal loss, lymphocyte infiltration and increased activation of microglia and astrocytes, as compared with control autopsies from subjects without liver or brain disease [ 66 , 67 ].…”
Section: Possible Mechanisms Behind Cognitive Dysfunction In Nafldmentioning
confidence: 99%
“…Modified Neurological Severity Score (mNSS), foot‐fault test and corner‐turning test were conducted to evaluate the functional outcome of mice at days 1 and 3 after ICH by two investigators blinded to the mouse groups as previously described 23,24 …”
Section: Methodsmentioning
confidence: 99%
“…Mice were given GW4869 solution at a dose of 2.5μg/g or equal volume of DMSO (3.75%) by intraperitoneal injection at days 0 and 2 after ICH. In mice subjected to Gr‐1 + cell depletion, 250 µg anti‐mouse Gr‐1 monoclonal antibody (MAb‐RB6‐8C5, BioXcell, West Lebanon, NH, USA) was given to each mouse by intraperitoneal injection one day before and one day after ICH surgery as we previously reported 23 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation